先化简再求值:a^2-b^2/a÷(a-(2ab-b^2/a))先化简,再求值:a^2-b^2/a÷(a-(2ab-b^2/a)),其中a=3,b=2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 13:53:26
先化简再求值:a^2-b^2/a÷(a-(2ab-b^2/a))先化简,再求值:a^2-b^2/a÷(a-(2ab-b^2/a)),其中a=3,b=2先化简再求值:a^2-b^2/a÷(a-(2ab-
先化简再求值:a^2-b^2/a÷(a-(2ab-b^2/a))先化简,再求值:a^2-b^2/a÷(a-(2ab-b^2/a)),其中a=3,b=2
先化简再求值:a^2-b^2/a÷(a-(2ab-b^2/a))
先化简,再求值:a^2-b^2/a÷(a-(2ab-b^2/a)),其中a=3,b=2
先化简再求值:a^2-b^2/a÷(a-(2ab-b^2/a))先化简,再求值:a^2-b^2/a÷(a-(2ab-b^2/a)),其中a=3,b=2
a^2-b^2/a÷(a-(2ab-b^2/a))
=(a+b)(a-b)/a×a/(a-b)²
=(a+b)/(a-b)
当a=3,b=2时
原式=(3+2)/(3-2)=5